Increasing Student Activeness Using The Cooperative Model TGT IPAS Class IV SDN Tambak Wedi 508 - Dita Widiastya Widiastya; Dita Rahmania Widiastya; Devina Oviana Dwi Agustin; Silvyulla Puspita Ambarsari; Agung Setyawan; Tehseen Mazhar (Journal of Action Research in Education, 2023)
This research is motivated by observational data that shows students' learning activity in IPAS material is very low. To respond to that, the researcher conducted a classroom action research aimed at improving students' learning activity. The objectives to be achieved in this research include: (1) To determine the improvement of students' engagement in learning through the use of lecture method, (2) To determine the improvement of students' engagement in the learning process through the use of cooperative learning model, specifically Teams Games Tournament (TGT). This research is a classroom action research. This research was conducted in class IVB with a total of 32 students, consisting of 17 male students and 15 female students. The research was conducted in 2 cycles, and the results showed an improvement in effectiveness in the second cycle. The change occurred because in the second cycle, students were more engaged in working together with their group, so there was less opportunity to discuss with other groups. This research measures several student learning skills, namely: questioning skills, answering skills, discussing skills, and group learning skills. The research findings show improvement in each domain in each cycle.The selection of this learning model is highly suitable and can enhance students' engagement in learning because in this learning model, students are not just passive listeners during the lesson, but they actively participate, think, learn, and compete among groups. This makes students challenged to win the competition and become active in learning.